Radiation Induces Valvular Interstitial Cell Calcific Response in an in vitro Model of Calcific Aortic Valve Disease - Meerman, Manon; Driessen, Rob; van Engeland, Nicole C. A.; Bergsma, Irith; Steenhuijsen, Jacco L. G.; Kozono, David; Aikawa, Elena; Hjortnaes, Jesper; Bouten, Carlijn V. C. (Frontiers in Cardiovascular Medicine, 2021)
Background: Mediastinal ionizing radiotherapy is associated with an increased risk of valvular disease, which demonstrates pathological hallmarks similar to calcific aortic valve disease (CAVD). Despite advances in radiotherapy techniques, the prevalence of comorbidities such as radiation-associated valvular disease is still increasing due to improved survival of patients receiving radiotherapy. However, the mechanisms of radiation-associated valvular disease are largely unknown. CAVD is considered to be an actively regulated disease process, mainly controlled by valvular interstitial cells (VICs). We hypothesize that radiation exposure catalyzes the calcific response of VICs and, therefore, contributes to the development of radiation-associated valvular disease. Methods and results: To delineate the relationship between radiation and VIC behavior (morphology, calcification, and matrix turnover), two different in vitro models were established: 1) VICs were cultured two-dimensional (2D) on coverslips in control medium (CM) or osteogenic medium (OM) and irradiated with 0, 2, 4, 8, or 16 Gray (Gy); and 2) three-dimensional (3D) hydrogel system was designed, loaded with VICs and exposed to 0, 4, or 16 Gy of radiation. In both models, a dose-dependent decrease in cell viability and proliferation was observed in CM and OM. Radiation exposure caused myofibroblast-like morphological changes and differentiation of VICs, as characterized by decreased αSMA expression. Calcification, as defined by increased alkaline phosphatase activity, was mostly present in the 2D irradiated VICs exposed to 4 Gy, while after exposure to higher doses VICs acquired a unique giant fibroblast-like cell morphology. Finally, matrix turnover was significantly affected by radiation exposure in the 3D irradiated VICs, as shown by decreased collagen staining and increased MMP-2 and MMP-9 activity. Conclusions: The presented work demonstrates that radiation exposure enhances the calcific response in VICs, a hallmark of CAVD. In addition, high radiation exposure induces differentiation of VICs into a terminally differentiated giant-cell fibroblast. Further studies are essential to elucidate the underlying mechanisms of these radiation-induced valvular changes.